Global Stability of Dynamic Systems of High Order - Benalili, M.; Lansari, A. (Symmetry, Integrability and Geometry: Methods and Applications, 2007)
This paper deals with global asymptotic stability of prolongations of flows induced by specific vector fields and their prolongations. The method used is based on various estimates of the flows.